Comparison of High-Protein, Intermittent Fasting Low-Calorie Diet and Heart Healthy Diet for Vascular Health of the Obese - Zuo, Li; He, Feng; Tinsley, Grant M.; Pannell, Benjamin K.; Ward, Emery; Arciero, Paul J. (Frontiers in Physiology, 2016)
Aim: It has been debated whether different diets are more or less effective in long-term weight loss success and cardiovascular disease prevention among men and women. To further explore these questions, the present study evaluated the combined effects of a high-protein, intermittent fasting, low-calorie diet plan compared with a heart healthy diet plan during weight loss, and weight loss maintenance on blood lipids and vascular compliance of obese individuals. Methods: The experiment involved 40 obese adults (men, n = 21; women, n = 19) and was divided into two phases: (a) 12-week high-protein, intermittent fasting, low-calorie weight loss diet comparing men and women (Phase 1) and (b) a 1-year weight maintenance phase comparing high-protein, intermittent fasting with a heart healthy diet (Phase 2). Body weight, body mass index (BMI), blood lipids, and arterial compliance outcomes were assessed at weeks 1 (baseline control), 12 (weight loss), and 64 (12 + 52 week; weight loss maintenance). Results: At the end of weight loss intervention, concomitant reductions in body weight, BMI and blood lipids were observed, as well as enhanced arterial compliance. No sex-specific differences in responses were observed. During phase 2, the high-protein, intermittent fasting group demonstrated a trend for less regain in BMI, low-density lipoprotein (LDL), and aortic pulse wave velocity than the heart healthy group. Conclusion: Our results suggest that a high-protein, intermittent fasting and low-calorie diet is associated with similar reductions in BMI and blood lipids in obese men and women. This diet also demonstrated an advantage in minimizing weight regain as well as enhancing arterial compliance as compared to a heart healthy diet after 1 year.